KOLABORASI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DENGAN LSM PERMATA LEMBATA DALAM MEREHABILITASI KORBAN KEKERASAN SEKSUAL DI KABUPATEN LEMBATA - Kristoforus Tueng Ruing; Frans Bapa Tokan; Eusabius Separera Niron (Journal Education and Government Wiyata, 2025)
This thesis is titled “Collaboration Between the Office of Women Empowerment and Child Protection and the Permata Lembata NGO in Rehabilitating Victims of Sexual Violence in Lembata Regency.” The main issue in this study is: “How is the collaboration between the Office of Women Empowerment and Child Protection and the Permata Lembata NGO in rehabilitating victims of sexual violence in Lembata Regency?” The purpose of this research is to describe the collaboration between the Office of Women Empowerment and Child Protection and the Permata Lembata NGO in rehabilitating victims of sexual violence in Lembata Regency. The theory used in this research is the theory of collaboration between the Office of Women Empowerment and Child Protection and the Permata Lembata NGO. The research method is descriptive with a qualitative approach. The technique for determining informants used in this study is the purposive sampling technique. The types of data are primary data and secondary data. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis techniques used include data reduction, data presentation, and finally, verification/conclusion drawing. The results of this study show that the collaboration between the Office of Women Empowerment and Child Protection and the Permata Lembata NGO in rehabilitating victims of violence against women and children in Lembata Regency can be carried out through: 1) Working together in the prevention of sexual violence: Providing education to prevent sexual violence, such as reproductive health education, socialization about sexually transmitted diseases, and self-protection education against sexual violence. 2) Working together in handling sexual violence: Providing legal assistance to victims of sexual violence and facilitating their social and individual reintegration so they can function effectively as members of society. Based on the analysis results above, the author concludes that the collaboration between the Office of Women Empowerment and Child Protection and the Permata Lembata NGO has shown good cooperation in efforts to prevent sexual violence and handle victims of sexual violence in Lembata Regency. However, this collaboration still requires improvement in several aspects to achieve more optimal results. One aspect that needs improvement is providing legal assistance for victims of sexual violence.